2004
DOI: 10.1016/j.jcrs.2004.06.049
|View full text |Cite
|
Sign up to set email alerts
|

In vivo digital imaging of the square-edged barrier effect of a silicone intraocular lens

Abstract: Early contact inhibition of LECs by a square-edged IOL design and its effects were demonstrated in vivo with sequential, high-resolution digital photography and commercially available graphics software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…[1][2][3][4][5] Tetz and Wildeck 6 made the first attempt to evaluate and quantify the edge structure of IOLs at the microscopic level. They experimentally evaluated the optimum microedge profile of an IOL to prevent lens epithelial cell (LEC) migration in culture.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Tetz and Wildeck 6 made the first attempt to evaluate and quantify the edge structure of IOLs at the microscopic level. They experimentally evaluated the optimum microedge profile of an IOL to prevent lens epithelial cell (LEC) migration in culture.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study based on similar digital photographs found a ''damming'' effect to migrating LECs at the square posterior edge at 1 month. 13 Our study was an objective assessment of LEC migration in relation to the square edge and enhanced edge of the optic. We put forward criteria by which these changes can be graded by digital photography.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies of cadaver eyes 4 found that IOLs with a truncated (squared) posterior optic edge provided a barrier to LEC migration along the posterior capsule. Since then, several studies [5][6][7] have confirmed that a sharp capsular bend formed when the capsule wraps around the sharp posterior edge of a square-edged IOL inhibits LEC migration, thus limiting the development of PCO.…”
mentioning
confidence: 99%